She Persisted Around the World : 13 Women Who Changed History - Chelsea Clinton (Bharat Penguin, 2018)
Women around the world have long dreamed big, even when they've been told their dreams didn't matter. They've spoken out, risen up and fought for what's right, even when they've been told to be quiet. Whether in science, the arts, sports or activism, women and girls throughout history have been determined to break barriers and change the status quo. They haven't let anyone get in their way and have helped us better understand our world and what's possible. In this book, Chelsea Clinton introduces readers to a group of thirteen incredible women who have shaped history all across the globe.
Keywords: No Poverty,Good Health And Well Being,Gender Equality,Responsible Consumption And Production,Peace Justice And Strong Institutions; Biography -- Biography